Patient-centered outcomes used in pediatric focused manual therapies research studies: a secondary data analysis of a systematic review - Beth Carleo; Kristian Anderson; Carol Parnell Prevost; Katherine A. Pohlman (SpringerOpen, 2021)
Abstract Background Patient-reported outcome measurements (PROM) are instruments that seek a patient's health or functional status. Inclusion of standardized PROMs in research studies and clinical practice provides a more comprehensive understanding of an intervention from the patient's viewpoint. This secondary analysis identified PROM usage and appropriateness of references for property measurements from clinical trials included in a recent systematic review of pediatric manual therapy. Methods All included manuscripts within a recent systematic review had two authors extract PROM and associated property measurement data, including the property measurements supporting citations. Inclusion criteria for the articles were published clinical trials (observational or experimental) of pediatric children receiving manual therapy (any profession) for any condition between 2001-March 2018. For each PROM's associated property measurement, two authors used the COSMIN study design checklist to appraise the quality of the cited study to evaluate the property measurement. Results Of the 50 manuscripts included in the systematic review, 20 manuscripts reported the use of 52 PROMs. Of the 52 PROMs assessed, 31 did not make a statement about the instrument's property measurement, 7 PROMs had property measurements stated but not referenced, 4 PROMs stated that the property measurement information was unknown, and 10 had property measurement data with reference(s). These 10 PROMs with referenced property measurements were from 7 unique PROMs: constipation assessment scale, satisfaction visual analog scale (VAS), crying time diary, sleep diary, fear avoidance belief questionnaire (FABQ), pain VAS, and autism treatment evaluation checklist. The assessment of the referenced property measurements found that several property measurement's dimensions had not been assessed and those that had were evaluated were done so with poor or fair standards. Conclusions This secondary analysis finds that clinical studies of pediatric manual therapy lack consistent use of PROMs with high quality property measurements. Further research to establish and implement PROMs to be used in future research studies and in clinical settings should become a priority for professions using manual therapy in children.